Nivel de conocimiento sobre el manejo odontológico de pacientes con diabetes mellitus por alumnos de VII y IX ciclo de la Facultad de Odontología de la UNAP - Loja Paredes, Daniel Elías (2024)
LEVEL OF KNOWLEDGE ABOUT THE DENTAL MANAGEMENT OF PATIENTS WITH DIABETES MELLITUS BY STUDENTS OF VII AND IX CYCLE OF THE FACULTY OF DENTISTRY OF THE UNAP By: DANIEL ELIAS, LOJA PAREDES y JAVIAR ENRIQUE,VELA VARGAS OBJECTIVE: Determine the difference in the level of knowledge about the dental management of patients with Diabetes Mellitus between seventh and ninth cycle students of the Faculty of Dentistry of the National University of the Peruvian Amazon. METHODOLOGY: This research used a quantitative, non-experimental, transversal, descriptive and comparative model. For this study, a sample of 73 students enrolled in the first semester of 2024 was used. Of these, 40 were in the seventh cycle and 33 in the ninth cycle, respectively taking adult clinics 1 and 3. As an instrument, an questionnaire was used approved by experts, which consisted of 20 questions categorized as low/bad, medium/regular and high/good. RESULTS: Among the results, a low level of knowledge was evident in both cycles with 69.9%%, regular with 27.4% and high with only 2.7%. Individually, the seventh cycle had results of 41.1% bad, 12.3% average and 1.4% good; In the ninth cycle the level of knowledge is 28.8% bad, 15.1% average and 1.4% good. CONCLUSIONS: It is concluded that the level of knowledge found in both study cycles is poor. Furthermore, no significant difference was found between the level of knowledge and the academic cycle.